Comparison Between Simple Closure and Subcutaneous Negative Pressure Drain Closure in Laparotomy Wound of Gastrointestinal Perforation (Eastern Medical College Journal, 2023)
Background: surgical site infection (SSI) is an infection that occurs after surgery in the part of the body where the surgery took place. SSI is very common in patients of perforation peritonitis if the wound is primarily closed in the setting of gross abdominal contamination. Even after thorough peritoneal irrigation with normal saline, the incidence of wound infection is high. If the wound infection is controlled, then many complications related to it could be prevented.Aim of the study: The aim of this study was to compare simple closure and subcutaneous negative pressure drain closure in laparotomy wounds of gastrointestinal perforation regarding the features, incidences, management, and outcomes.Methodology: This clinical trial study was conducted at the surgical units of Dhaka Medical College Hospital, Dhaka, Bangladesh during the period from July 2014 to June 2015. A total of 108 cases were selected by inclusion criteria. All the patients were divided in two groups; group A-where negative suction drain was not used and Group B-where a negative suction drain was used in the subcutaneous space at the time of closure of the abdomen after perforation and thorough peritoneal toilet. As per the inclusion criteria of this study patients undergoing emergency laparotomy due to gastrointestinal perforation, aged up to 60 years old, non-diabetic, non-anemic, normal renal function, non-jaundiced and normal nutritional status were included. The outcome compared in the form of wound infection, hospital stay, second surgery and morbidity.Results: In this study, the average rate of SSI was found 55.76% (29/52) in group A and 30.36% (17/56) in group B. Average hospital stay for group A and group B were 19 days and 12 days respectively. Second surgery was needed in 4 cases in group A and for 8 cases in group B. The second surgery was done in the form of secondary suturing of wound or wound dehiscence and burst abdomen repair. Mortality in group A was 8 and in group B it was 4; but it was not related to SSI because all death occurred within 3 days after surgery mainly due delay presentation and to poor general condition pre-operatively. Overall morbidity was less with negative pressure closure compared to simple closure and it highly affects the morbidity and somehow mortality also.Conclusion: The application of a subcutaneous negative pressure drain may be effective in preventing superficial surgical site infection and may reduce hospital stay, treatment cost, morbidity, and mortality. There is more chance of wound infection in such laparotomy wound because of highly contamination of the peritoneal fluid with fecal material. Such wound constantly leads to serous discharge and bacterial colonization. But negative pressure closure removes that collection and avoids wound infection, and it helps in reducing hospital stay and morbidity.Eastern Med Coll J. July 2023; 8 (2):43-47